A study of risk factors in acute myocardial infarction of adults ages 18 to 45 in a tertiary referral centre for cardiology services in Malaysia's East Coast. - Mohd Razib, Mohd Zhafri; Draman, Samsul; Abdullah, Aszrin; Mohd. Shah, Aida Nur Sharini; Mohamed Bakrim, Norbaiyah; Wan Omar, Wan Fatein Nabeila; Ab Rahman, Jamalludin; Z, Mohamad (International Islamic University Malaysia, 2022)
INTRODUCTION: Acute myocardial infarction (AMI) is the major cause of death worldwide. There is limited data on the characteristics of afflicted young adults. A recent increase in recreational drugs has been associated. No local studies have ever reliably attributed this to young adults. This study aims to study the characteristic of AMI cases among young adults and these associations. MATERIALS AND METHODS: This cross-sectional study was conducted at a tertiary referral centre for Cardiology services, Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang. It involved screening 818 patients presenting with AMI at the Emergency Department of HTAA over a one-year duration. Malaysian citizens aged 18 to 45 years newly diagnosed with AMI were included. Urinary samples were collected for recreational drug screening. RESULTS: The incidence of AMI cases among young adults in HTAA Kuantan, Pahang were 10.3 per 100 persons of total AMI cases in one year (95% Confidence Interval, 8.4%-12.6%). Fifty -eight patients who met the inclusion criteria were recruited, 1.7 % tested positive for amphetamines. Males made up 96.6% of the patients and the most common risk factor identified for young adults with AMI was smoking (N=45, 77.6%) followed by obesity (N=33, 56.9%). More than half (58.6%) of the patients had 3 cardiovascular disease risk factors or more. CONCLUSION: Recreational drug use at AMI presentation was negligible. Males made up the majority and smoking was the most prevalent risk factor. To date, this is the first study in Malaysia looking at the incidence of young adults with AMI and their preponderant characteristics.